Slovenski esej: kronološki uvid terminoloških rešitev - Laznik, Anita (Slavia Centralis, 2020)
The Slovenian Essay: A Chronological Overview of Terminological SolutionsThe essay is a specific genre which is beneficial for the study of literature in those areas of research literature that cannot be dealt which solely through scientific discussion. This article presents solutions for the terminological variability pertaining to the essay in Slovenian literary studies, namely, by presenting a chronological overview of published discussions that have appeared in book form – from Esej in Literarni leksikon to Miran Štuhec’s Slovenska esejistika v drugi polovici dvajsetega stoletja.
Keywords: essay; essay writing; chronology; literary science